2008
DOI: 10.1186/1471-2199-9-81
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of two LY-6 family genes by intron retention and transcription induced chimerism

Abstract: Background: Regulation of the expression of particular genes can rely on mechanisms that are different from classical transcriptional and translational control. The LY6G5B and LY6G6D genes encode LY-6 domain proteins, whose expression seems to be regulated in an original fashion, consisting of an intron retention event which generates, through an early premature stop codon, a non-coding transcript, preventing expression in most cell lines and tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…LY-6 superfamily members are cysteine-rich, generally GPI-anchored, cell surface proteins, which have definite or putative immune-related roles [15]. Among these LY-6 MHC class III region genes, Ly6g5b showed a particular behaviour in the regulation of its expression [13,16], involving an intron retention event in human and mouse, the rarest form of alternative splicing found in metazoan species [17]. The intron retained is the first one after the initial exon and interrupts the open reading frame (ORF) just after the signal peptide introducing a premature stop codon (PSC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LY-6 superfamily members are cysteine-rich, generally GPI-anchored, cell surface proteins, which have definite or putative immune-related roles [15]. Among these LY-6 MHC class III region genes, Ly6g5b showed a particular behaviour in the regulation of its expression [13,16], involving an intron retention event in human and mouse, the rarest form of alternative splicing found in metazoan species [17]. The intron retained is the first one after the initial exon and interrupts the open reading frame (ORF) just after the signal peptide introducing a premature stop codon (PSC).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a PSC at this position should cause this intron-retained transcript to undergo Nonsense Mediated Decay (NMD) [18,19]. However, this transcript seemed to escape NMD and was more abundant than the correctly spliced mRNA [13,16]. In addition, findings in our laboratory showed the presence of LY6G5B gene exons in transcripts derived from the upstream gene CSNK2B [16], which encodes the Casein Kinase II β subunit , a ubiquitous protein kinase which regulates metabolic pathways, signal transduction, transcription, translation, and replication [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR is the least characterized event of all AS types, mainly because of the exclusion of this phenomenon in many studies, due to the difficulties to differentiate it from incompletely processed transcripts. 7 However, many discoveries have been made about IR in recent years, including studies focusing human diseases. Here, I review the most recent studies about IR, and my aim is to provide some useful information for future research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was revealed that intronretained transcripts of LY6G5B and LY6G6D are not subjected to NMD, but form chimeric transcripts with adjacent genes' transcripts respectively, and regulate the expression of two genes. 7 …”
Section: Intron Retention Regulates Gene Expressionmentioning
confidence: 99%